Analisis Aspek Perkembangan Kognitif Dan Motorik Dalam Permainan Jump Count Melalui Abacus Tangga - Ririn Dwi Wiresti; Suyadi Suyadi (Jurusan PIAUD IAIN Syekh Nurjati Cirebon, 2021)
A child with an age range of 0 to 6 years is considered in the Early Childhood period that needed a lot of development stimulation. Following the regulation of the Minister of Education and culture (Permendikbud) No. 137 of 2014, there are six aspects of child development, namely physical-motor, religious and moral values, language, art, motor, and cognitive. In its application several points of progress can be stimulated simultaneously. For example, in coloring activities, points of development that was stimulated are excellent motor and art. In reality sometimes there is a separation between the practice of cognitive and motor development. For example, cognitive development stimulated through indoor exercise, while motor development will be encouraged through free exercise. Cognitive and motor development are interconnected aspects. Through these examples, researchers created the Jump Count game through the abacus ladder media. This game aims to dissect cognitive and motor indicators in depth. This research uses the descriptive quantitative method. The results of the study based on the instrument filling data with a check indicator on the cognitive and motor development of children aged 5 – 6 years; the data is presented in the form of a percentage. This research conducted in Raudatul Athfal (RA / Kindergarten) of Bunayya Yogyakarta with the research subjects of 14 children from the class of B2. The result showed that the Jump Count game could improve children's cognitive development by 34.1 % and children's motor development by 36.7 %. It can concluded; this game can improve cognitive development, fine motor, and gross motor skills in children with an age range of 5 – 6 years.